PERAN PEKERJA SOSIAL TERHADAP PENANGANAN ANAK KORBAN KEKERASAN SEKSUAL: PENDEKATAN TEORI SISTEM DI PERLINDUNGAN PEREMPUAN ANAK KOTA MAKASSAR - AB, Syamsuddin (Social Welfare Study Program, 2025)
The role of social workers in handling children victims of sexual violence aims to determine and describe the role of social workers in handling children victims of sexual violence at the Regional Technical Implementation Unit for the Protection of Women and Children in Indonesia. Methodologically, this type of qualitative research has two data sources, namely primary and secondary data sources, the approach used is systems theory. The instrument is the researcher himself, data collection through observation, interviews and documentation, data analysis through the data reduction stage, data presentation, drawing conclusions. The research results show the role of social workers in assisting clients who are victims of sexual violence. The first step is providing public complaint services, assistance and counseling for clients based on the type of case, psychological consultations related to the client's needs, legal consultations, providing medical assistance, assistance in safe houses (shelters) and rehabilitation, home visits and social reintegration for clients, carrying out psychoeducation, In conclusion, social workers intensively carry out initial assessments through to determination and follow-up through psychoeducation so that clients can return to their functioning in the family and community. The implication is that the government is expected to provide greater support, both financially and in the provision of health services. Supporting the prevention of sexual violence requires special attention to client administration to ensure more effective data recording and reporting, and the importance of protecting clients in Makassar Keywords: Role, Social Worker, Violence, Child Sexual, System